Níveis plasmáticos de BDNF em idosas com e sem dor lombar aguda e sua relação com intensidade da dor, sintomas depressivos e uso de medicamentos analgésicos e antidepressivos - Juliano Bergamaschine Mata Diz (2016)
Low back pain (LBP) is a multifactorial symptom that has emerged as a major public health problem in the older population worldwide. It affects between 3050% of the older adults aged 60 years and is strongly associated with the presence of disabling pain and depressive disorders. Contemporary research has sought to identify the multiple biological mechanisms involved in LBP complaints. This study compared brain-derived neurotrophic factor (BDNF) plasma levels, a key neurotrophin in pain modulation, between older women after an acute episode of LBP and controls without pain, and investigated potential differences in BDNF levels between controls and LBP subgroups divided according to pain severity, presence of depressive symptoms and current use of analgesic and antidepressant drugs. This is a cross-sectional observational study including 221 community-dwelling older women aged 60 years and older (i.e. 154 with an acute episode of LBP and 67 controls without pain). Sociodemographic and clinical variables were obtained by using a multidimensional questionnaire that included age, schooling, marital status, BMI, physical activity and numbers of comorbidities and medications in use. Pain severity "at the present time" of data collection and "over the past week" before data collection was assessed by using an 11-point Numeric Rating Scale (NRS 010). The scores of NRS 010 were re-coded in three levels of pain severity: mild pain (03); moderate pain (47); and severe pain (810). The presence of depressive symptoms was assessed by using the 15-item Geriatric Depression Scale (GDS-15). BDNF plasma levels were measured with an ELISA kit. The age of participants ranged from 62 to 88 years (mean ± SD of 70.8 ± 5.3). There was no significant difference between controls and LBP group with regarding to age, schooling and marital status. BDNF levels in LBP group were significantly higher as compared to controls (7515.9 ± 3021.2 vs 6331.8 ± 3364.0 pg/mL, p=0.005). The estimated mean difference between the two groups was 1184.1 (95% CI 281.7 to 2086.5) pg/mL. BDNF levels were significantly higher in LBP subgroups as compared to controls, regardless of whether pain severity was mild, moderate or severe "at the present time" (p=0.005, p=0.044 and p=0.030, respectively) and "over the past week" (p=0.024, p=0.022 and p=0.029, respectively); if there was presence (p=0.029) or absence (p=0.003) of depressive symptoms; and if participants made current use (p=0.019) or not (p=0.008) of analgesic drugs. However, there were no significant differences in BDNF levels among LBP subgroups with mild, moderate and severe pain at both pain assessment periods (p>0.05); presence or absence of depressive symptoms (p=0.758); and with or without the current use of analgesic drugs (p=0.589). On the other hand, BDNF levels were significantly higher in LBP subgroup without the current use of antidepressant drugs as compared to LBP subgroup with the current use of antidepressant drugs (p=0.046) and controls (p=0.008). However, there was no significant difference in BDNF levels between LBP subgroup with the current use of antidepressant drugs and controls (p=0.442). The results support the increased BDNF plasma levels in older women after an acute episode of LBP. BDNF levels were not associated with pain severity, presence of depressive symptoms and with the current use of analgesic drugs. Future studies should investigate the mechanisms that lead to increased BDNF plasma levels in older women with acute LBP. Additionally, for clinical settings, the aware that the occurrence of LBP in older adults is an intricate and multifactorial symptom, with associated factors that go beyond the musculoskeletal and biomechanical aspects should be considered by physiotherapists and health professionals both in assessment issues as in therapeutic approaches focused to this population.